The Moderating Role Of Firm Size On Relationship Between Majority Ownership And Debt Policy Of Property Sector - Perdana Wahyu Santosa; Harry Budiantoro; Alyta Shabrina Zuzryn (Fakultas Ekonomi dan Bisnis, Universitas Tarumanagara, 2022)
This study aims to understand well the effect of majority ownership and firm size on financial fundamentals as controlling the debt policy of the property sector in Indonesia. The data panel model was built using data from firms listed in the property sector of the Indonesia Stock Exchange. Data is extracted from audited quarterly financial reports from 2014-2019. The results show that majority ownership negatively influences debt policy. In general, majority ownership negatively affects the capital structure in the short and long term because management is more prudent. However, sales growth and firm size insignificantly affect debt policy. Moreover, the moderate effect of firm size on the relationship between majority ownership and debt policy was strengthened. The controlling fundamentals, namely liquidity and profitability, negatively affect leverage. However, price to book value positively affects leverage. Our main implication is that majority ownership and firm size with firm-specific rather than country facts explain the differences in debt policy in the property sector.